Maintenance therapy with trofosfamide, idarubicin and etoposide in patients with rhabdomyosarcoma and other high-risk soft tissue sarcomas (CWS-2007-HR): a multicentre, open-label, randomised controlled phase 3 trialResearch in context - Ewa Koscielniak; Gustaf Ljungman; Bernarda Kazanowska; Felix Niggli; Monika Sparber-Sauer; Rupert Handgretinger; Martin Zimmermann; Joachim Boos; Bernd Blank; Erika Hallmen; Irene Teichert von Lüttichau; Irene Schmid; et al. (EClinicalMedicine)
Summary: Background: Rhabdomyosarcoma and other soft tissue sarcomas (STS) with high-risk features are still associated with an unsatisfactory outcome. We evaluated the efficacy of oral maintenance therapy added at the end of standard therapy in patients with high-risk rhabdomyosarcoma and STS. Methods: CWS-2007-HR was a multicentre, open-label, randomised controlled, phase 3 trial done at 87 centers in 5 countries. Eligible patients were those aged 6 months to 21 years with non-metastatic incompletely resected embryonal rhabdomyosarcoma occurring in unfavourable sites with unfavourable age (≥10 years) and/or tumour size (>5 cm); all non-metastatic alveolar rhabdomyosarcoma and those with any non-metastatic rhabdomyosarcoma with nodal involvement. A further group was also eligible: patients with non-metastatic undifferentiated sarcoma, extraskeletal Ewing sarcoma and primary unresected synovial sarcoma. Patients in complete remission at the end of standard therapy (nine cycles of ifosfamide, vincristine with doxorubicine or dactinomycin, and surgery or radiotherapy, or both) were randomised to either stop treatment (S-arm) or to receive oral maintenance therapy (M-arm) with eight 10-day courses (25 weeks) of trofosfamide (2 × 75 mg/m2/day) and idarubicin (1 × 5 mg/m2/day 1,4,7,10) alternating with trofosfamide and etoposide (2 × 25 mg/m2/day). The primary outcome was event-free survival (EFS) and the secondary outcome was overall survival (OS) in the intent-to treat population. This trial is registered at ClinicalTrials.gov, NCT00876031, and, EudraCT 2007-0001478-10. Findings: Between July 1st, 2009 and June 30th, 2019, 195 patients were randomly assigned to the M-arm (n = 96) or S-arm (n = 99). In the intent-to-treat population, with a median follow-up of 5.2 years (IQR 3.9–6.1) for surviving patients, the 3-year EFS in the M-arm was 66.9% (95% CI 58.1–77.2) versus 75.6% (67.6–84.6) in the S-arm (hazard ratio, (HR) 1.62, 95% CI 0.98–2.69, p = 0.06). 3-year OS was 82.8% (95% CI 75.4–90.8) in the M-arm versus 84.7% (95% CI 77.8–92.1) in the S-arm (HR 1.55, 95% CI 0.84–2.89, p = 0.17). Grade 3–4 adverse events were haematological in 66% of patients, febrile infections in 6%, gastrointestinal in 10%, and sensory neuropathy in 1%. Interpretation: The addition of 25 weeks of oral maintenance therapy with trofosfamide, etoposide and idarubicin after standard therapy does not improve EFS and OS in patients with high-risk rhabdomyosarcoma and other STS. Funding: Deutsche Kinderkrebsstiftung Grant No.DKS 2009.09, DKS 2012.06, DKS 2015.13, DKS 2018.10 and DKS 2021.04.